Concept and application of Shariah for the construction industry: shariah compliance in construction contracts, project finance and risk management - Abdul Rashid, Khairuddin (World Scientific Publishing Co. Pte. Ltd., 2019)
The application of Shariah compliance in business transactions continues to increase. The Asian financial crisis of 1997, global financial crisis of 2007–2008, Enron scandal and other reported ills besieging conventional business transactions have led to advocates of Shariah-compliant business transactions promoting the latter as a credible alternative. However, unlike the banking, commerce and financial sectors, the uptake by the construction sector was sluggish due to limited understanding of Shariah among the practitioners and policymakers compounded by the lack of research and publications on its application for the construction sector.